Evaluating financial performance: ratio analysis. A case of Agrobank / Suhaila Mohd Shangki - Mohd Shangki, Suhaila (2011)
Agro bank is an institution which provides holistic financial services and banking facilities. They give their utmost priority to the needs of their customers by providing attractive products and services such as savings activities, banking services, loan facilities, insurance coverage and advisory services. Agro bank is a continuity of the former Bank Pertanian Malaysia which has 40 years of experience in agricultural banking and an excellent track record in shaping and developing successful entrepreneurs. With a wide network of branches throughout Malaysia, they are confident of providing the best services to all. Researcher has chosen financial performance analysis of Agro bank as the topic .The aim of this paper is to examine and analyze performance of the company either good or worse. Financial analysis is the most important way for company to analyze and evaluate the performance of the company. The methods to measure financial performance are by using quantitative analysis which is ratio analysis. The part of ratio analysis is liquidity performance, profitability performance, debt performance and also operating performance. Ratio analysis is one of the techniques of financial analysis to evaluate the financial condition and performance of a business concern. Simply, ratio means the comparison of one figure to other relevant figure or figures. The statement are detail and do not present the required information at a glance. Ratio analysis is therefore an attempt to present the information of financial statement is simplified, systematized and summarized form. The result indicates that, the used of these methods contribute to the reasons and evidence that based on the trend of financial statement.